REVERBERATION TIME IN COMBINED LECTURE ROOMS - Sabtalistia, Yunita Ardianti (Border: Jurnal Arsitektur, 2024)
The size of the reverberation time is determined by the volume of the room and the type of surface material in the room. Lecture rooms at 701 and 702, Building L, 7th Floor, Bachelor of Architecture Study Program, Tarumanagara University have lecture rooms dominated by glass windows with aluminum frames on both sides of the room and exposed concrete beams and columns. These materials tend to increase reverberation time. Apart from that, the two lecture rooms are also often used simultaneously. Using both lecture rooms simultaneously will increase the volume of the room. The larger the room volume also increases the reverberation time. This research aims to optimize the reverberation time of 2 lecture rooms that are used simultaneously. Lecture rooms and the types of materials forming the rooms were experimented with using Ecotect. Lecture rooms 701 and 702 were used as research samples. The number of occupants in the class was counted as 80 people because not all the tables were filled with students. The research results show that combining 2 lecture rooms causes problems with reverberation time. The reverberation time in existing conditions is 1.11 seconds. To overcome the high reverberation time, it was necessary to replace the ceiling covering from gypsum to acoustic in lecture room 701. After replacing the ceiling, the reverberation time decreased to 0.74 seconds. This value is close to the optimal reverberation time which has a value of 0.77 seconds.